2017
DOI: 10.1074/jbc.m116.764274
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Kirklareli (α H58L), a New Variant Associated with Iron Deficiency and Increased CO Binding

Abstract: Edited by F. Peter GuengerichMutations in hemoglobin can cause a wide range of phenotypic outcomes, including anemia due to protein instability and red cell lysis. Uncovering the biochemical basis for these phenotypes can provide new insights into hemoglobin structure and function as well as identify new therapeutic opportunities. We report here a new hemoglobin ␣ chain variant in a female patient with mild anemia, whose father also carries the trait and is from the Turkish city of Kirklareli. Both the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…The imidazole sidechain of αHis58 provides stability to the heme bound O 2 through hydrogen-bond interactions, which is lost with αLeu58. Indeed, the crystal structure of Hb Kirklareli shows that the bound O 2 is no longer stabilized, consistent with the observed increased autoxidation and loss of hemin ~200 times more rapidly than native α subunits (Bissé et al 2017). Interestingly, Hb Kirklareli α subunit has an ~80,000-fold higher affinity for CO than O 2 , causing it to rapidly take up and retain carbon monoxide (Bissé et al 2017).…”
Section: Hemoglobin Variants With Altered Oxygen Affinitysupporting
confidence: 52%
See 1 more Smart Citation
“…The imidazole sidechain of αHis58 provides stability to the heme bound O 2 through hydrogen-bond interactions, which is lost with αLeu58. Indeed, the crystal structure of Hb Kirklareli shows that the bound O 2 is no longer stabilized, consistent with the observed increased autoxidation and loss of hemin ~200 times more rapidly than native α subunits (Bissé et al 2017). Interestingly, Hb Kirklareli α subunit has an ~80,000-fold higher affinity for CO than O 2 , causing it to rapidly take up and retain carbon monoxide (Bissé et al 2017).…”
Section: Hemoglobin Variants With Altered Oxygen Affinitysupporting
confidence: 52%
“…Mutations in the heme pocket are also known to affect Hb oxygen binding properties (Thom et al 2013). An example is Hb Kirklareli (αHis58Leu), which is associated with iron deficiency and increased CO binding (Bissé et al 2017). The imidazole sidechain of αHis58 provides stability to the heme bound O 2 through hydrogen-bond interactions, which is lost with αLeu58.…”
Section: Hemoglobin Variants With Altered Oxygen Affinitymentioning
confidence: 99%
“…This effect was supported in vivo by data showing that upon CO treatment or after HO-1 induction, the levels of extracellular free heme in the circulation, significantly increased by the infection, nearly returned to basal values. Most striking are very recent data published by Bisse and colleagues (12) supporting this concept in humans. The authors identified a new mutated form of Hb (Hb Kirklareli) in a female patient and her father.…”
Section: Co As a Protector Of Heme Oxidationmentioning
confidence: 83%
“…A biochemical analysis of Hb Kirklareli shows that the mutant ␣-subunit of the protein autooxidizes~8 times more and loses heme~200 times faster than the native subunit. Interestingly, the affinity of Hb Kirklareli for CO is~80,000-fold higher than for O 2 , explaining why the father, being a smoker, is protected against heme oxidation and Hb denaturation (12).…”
Section: Co As a Protector Of Heme Oxidationmentioning
confidence: 99%
“…Over the years, control and management of Hb disorders have encountered major economic and organizational difficulties [18]. Mutations in hemoglobin can cause a wide range of phenotypic outcomes, including anemia due to protein instability and red cell lysis [19] and occlusion of the microvascular circulation leading to tissue ischaemia, infarction, and chronic hemolytic anemia [20]. Knowledge in hemoglobin variants and carrier status is thus necessary in reproductive decision making to modify risk for offspring of serious conditions such as sickle cell anemia as well as provide direct health benefit to carriers [21].…”
Section: Discussionmentioning
confidence: 99%